2014
DOI: 10.7314/apjcp.2014.15.9.4045
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF-β1 in Human Colorectal Cancer and Effects after Cantharidinate Intervention

Abstract: Effects of transforming growth factor-beta (TGF-β) were investigated in human colorectal cancer, and the influence of cantharidinate in inhibiting TGF-β1 expression was explored. Relationships among TGF-β1 and sex, age, tumor size, tumor location, tumor stage were also analyzed. H&E and immunohistochemistry staining were employed to assess colorectal cancer and TGF-β1 expression, respectively. Then, HCT-116 CRC cells were randomly divided into four groups, controls, no serum-treated, chemotherapy and cantharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…In the CRC patients included in the study group, TGFβ1 expression level in the tumor tissue was higher than in the adjacent normal tissue, although not statistically signi cant. Literature data present TGFβ1 as being related to tumor size and tumor location [25]. In our study, we observed an overexpression of this gene in the tumor samples, but this was not statistically signi cant.…”
Section: Discussioncontrasting
confidence: 67%
“…In the CRC patients included in the study group, TGFβ1 expression level in the tumor tissue was higher than in the adjacent normal tissue, although not statistically signi cant. Literature data present TGFβ1 as being related to tumor size and tumor location [25]. In our study, we observed an overexpression of this gene in the tumor samples, but this was not statistically signi cant.…”
Section: Discussioncontrasting
confidence: 67%
“…Malignancies such as CRC are currently considered an important area of study, due to the burden of the disease and the mortality rate (2)(3)(4)(5). In numerous types of cancer, it has been established that aberration in genes encoding TGF-β signaling components can contribute to colon carcinogenesis in humans (7,8). This signaling pathway controls numerous cellular functions, including epithelial cell proliferation, apoptosis and migration, in addition to tumor initiation, progression and metastasis (8,9), making it a suitable target for cancer therapy (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…and Smad3 components associates with Smad4, and these translocate to the nucleus to activate the transcription of downstream target genes (7)(8)(9). It is well-established that growth factors with a broad range of cellular effects, such as TGF-β, must be subject to extensive regulation to control their expression and function.…”
Section: Modulation Of Transforming Growth Factor-β Signaling Transdumentioning
confidence: 99%
See 1 more Smart Citation
“…Among the multitude of different signaling molecules found in the blood, transforming growth factor-β (TGF-β) is known to aggregate metastasis by promoting epithelial-mesenchymal transition (EMT) and the invasiveness of primary carcinomas (9). TGF-β1, an ubiquitous cytokine, induces cancer cells to proliferate and promotes them to form an invasive phenotype (10,11). TGF-β ligands are secreted from cells in three isoforms (TGF-β1, TGF-β2, TGF-β3), with the latency associated protein (LAP), which makes these isoforms inactive.…”
Section: Introductionmentioning
confidence: 99%